2020
DOI: 10.1186/s12955-020-01571-1
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Short HIV Stigma scale in Brazilian Portuguese

Abstract: Background HIV-related stigma, or the degree to which people living with HIV endorse negative stereotypes associated with HIV, is associated with poor continuum of care outcomes. We translated the 12-item Short HIV Stigma scale and evaluated its psychometric properties in a Brazilian context with regard to construct validity and reliability. Methods The first step included translation, back-translation, evaluation, peer review, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 48 publications
0
33
0
2
Order By: Relevance
“…Twenty-four of the included studies [ 20 , 22 , 23 , 39 , 40 , 45 , 63 , 69 , 70 , 91 , 92 , 93 , 95 , 97 , 107 , 111 , 118 , 121 , 144 , 146 , 147 , 171 , 178 , 184 ] were development and/or validation studies of the HSS and/or its abbreviated versions. The remaining studies were observational or experimental studies that used the HSS to assess HIV-related stigma in different contexts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four of the included studies [ 20 , 22 , 23 , 39 , 40 , 45 , 63 , 69 , 70 , 91 , 92 , 93 , 95 , 97 , 107 , 111 , 118 , 121 , 144 , 146 , 147 , 171 , 178 , 184 ] were development and/or validation studies of the HSS and/or its abbreviated versions. The remaining studies were observational or experimental studies that used the HSS to assess HIV-related stigma in different contexts.…”
Section: Resultsmentioning
confidence: 99%
“…For internal consistency, all the studies, except a 4-item scale in one study [ 127 ] and some subscales in ten studies [ 23 , 52 , 68 , 69 , 91 , 111 , 170 , 172 , 176 , 189 ], reported Cronbach’s alphas of above the recommended acceptable threshold of 0.70 [ 191 ]. Two studies [ 34 , 95 ] reported the internal consistency of the HSS using McDonald’s omega instead of Cronbach’s alpha and reported good reliability ( Table 1 and Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can confidently compare means and conclude that any difference between the unidimensional HSS-10 across sex and age groups comes from a real difference in HIV stigma and not from the measure's group-specific properties. Although various studies have used the 40–item HIV stigma scale [ 19 ] and the 12-item HIV stigma scale [ 20 , 44 ] to assess stigma and reported their psychometric properties, no study has been found to report the measurement invariance of the tool. Therefore, future research involving HIV stigma assessment tools should use robust psychometric analytical models involving measurement invariance.…”
Section: Discussionmentioning
confidence: 99%
“…We performed translation of RHS items to Brazilian Portuguese following established guidelines (Beaton et al, 2000). Details of translation procedures were described elsewhere (Luz et al, 2020;Torres et al, 2021). A qualitative pretesting of the translated items was conducted with a small convenience sample to ensure item comprehensibility before moving into the reliability and construct validity step.…”
Section: Translationmentioning
confidence: 99%